The T.R.E.E Principles - Arif Pratiwindyo (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
Health and Physical Education (HPE) is one of the lesson which become part of the integral in total education in order to develop physical fitness, social mental,also emotional as well in order to create Indonesian people completely through physical activity’s vehicle as a shape from interaction’s process among learners with sphere through physical activitis that arranged systematically. So that HPE has it’s roles such as: life long education utility, life long health utility, life long skill utility. To solve various obstacles during learning HPE such as diversity in learner’s conditions, diversity of facilities and infrastructures, and also the condition of school’s environment we could apply The T.R.E.E. Principles that stand for Teaching Styles, Rules and Regulations, Environments, and Equipments.